2020
DOI: 10.1055/s-0040-1707813
|View full text |Cite
|
Sign up to set email alerts
|

Application of α-Amino-β-fluorophosphonates in Construction of their Dipeptide Analogues

Abstract: Herein, we present application of α-amino-β-fluorophosphonates for the construction of their dipeptide analogues. α-Amino-β-fluorophosphonates were prepared in a XtalFluor-E mediated deoxyfluorination of α-hydroxy-β-aminophosphonates. The reaction proceeds through an aziridinium ion formation, which was confirmed by the formation­ of a hexacoordinate phosphorus compound. Moreover, the absolute configuration of the obtained compounds was determined by X-ray analysis, which proved the stereochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Recently, a report revealed that the same strategy is applicable to realize stereoselective and regioselective synthesis of α-amino-β-fluorophosphonates [ 60 ].…”
Section: Synthetic Application Of Aziridinium Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a report revealed that the same strategy is applicable to realize stereoselective and regioselective synthesis of α-amino-β-fluorophosphonates [ 60 ].…”
Section: Synthetic Application Of Aziridinium Ionsmentioning
confidence: 99%
“…The schemes below (Schemes 15 and 16) show the formation of aziridinium ylides (55 and 59) via intramolecular or intermolecular addition of diazoacetate (54 or 58) to aziridine (54 or 57) with metal catalysts. Subsequent ring openings initiated by the anion at the α-position of carboxylate give ring-expanded products (56) and (60) [75][76][77].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…19 The main objective of this work was further extension of our previous studies on the regioselective fluorination of α-hydroxy-β-aminophosphonates (Scheme 1) and application of the resulting compounds as potential tools in the synthesis of their dipeptide analogues. [20][21][22][23][24] In this paper, we would like to present some transformations of α-hydroxyγ-aminophosphonates which took place in reactions with DAST and PyFluor (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are many examples of various properties and biological activities of phosphonic acid derivatives containing a hydroxyl group [ 19 , 20 ] and/or fluorine atom in α position to a phosphonate group [ 21 , 22 , 23 , 24 , 25 , 26 ]. These compounds are also isosteric analogues of natural products [ 27 ] and enzyme inhibitors ( Figure 2 ) [ 19 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are also isosteric analogues of natural products [ 27 ] and enzyme inhibitors ( Figure 2 ) [ 19 , 28 ]. There are also examples of phosphonate derivatives having a fluorine atom in a β position to a phosphorus atom [ 24 , 29 , 30 ] and fluorinated or nonfluorinated unsaturated phosphonates [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%